Análise dos internamentos em um centro de referência de assistência ao queimado no Norte do Paraná no ano de 2012 - Oussaki, Flávia Mendonça da Silva (2014)
The burn produces severe functional, aesthetic and psychological sequelae. The specialized care to highly complex individual burned was encouraged by GM / MS No. 1273, of November 21, 2000, as well the creation of Burn Treatments Centers (CTQ). The aim of this study was to analyze the CTQ admissions occurred in the north of Paraná in 2012, identifying the personal characteristics of burn victims, the characterization of burns, care demands and loco regional insertion service. Quantitative, cross-sectional descriptive study involving 310 clinical records as sources, investigated from January to March 2013, after approval by the Ethics and Research Committee. Data were analyzed using descriptive statistics, with variables organized in a spreadsheet Excel version 2010 and illustrated in image and tables. The results showed that the service demands of absorbed 82% (18) of the 22 health districts in the state with a delay of entry into service equal to or greater than three days after the accident in 43% (112) of cases. Predominated in 65% (202) were male and 55% (170) of adults, with the prevailing domestic alcohol and scald with superheated liquid as major cause of accidents. As for morbidity and mortality, 47% (146) of the patients had 2nd degree burns and 53% (164) of 3rd degree; there were 34 deaths, 53% (18) in men and 47% (16) in women. The mean hospital stay was 13 days and bed occupancy of 78.3% in service. Treatment was developed by a multidisciplinary team, including actions as drug therapy, dressings, surgery and use of invasive devices. Since admission begins the rehabilitation process that follows with outpatient care for years, and 14% (45) of the patients perform reconstructive surgeries in outpatient. It has been argued that burn injuries represent a serious health problem and a challenge for public policy and the health care system. The specialized treatment is a high cost, but several advances and the availability of care technologies and qualification of care have improved the survival and quality of life of patients, favoring the prognosis and harm reduction. Emphasize some weaknesses as a delay in the construction of all CTQs planned in 2000; delays in the availability of specific technologies of care; better qualification of health services in the initial care and outpatient victims in places of origin; greater speed and safety in logistics such as transportation systems and therapeutic support. Regarding the analyzed service, it is a place of excellence in service to the burnt, with some aspects to improve. It is concluded that a priority in the treatment of burned patients refers to the speed, quality and continuity of care, which justifies the deployment of CTQs and organizing services on a macro-regional network of health care. Epidemiological studies, identifying groups and local risk factors may still subsidize preventive campaigns, reducing the number of burn admissions or by changing your profile linked to the severity of injuries.